Characterization of iatrogenic polypharmacy in the elderly as a public health problem: A literature review (Research, Society and Development, 2024)
Introduction: Iatrogenic is defined as any pathological modification, adverse effect, or complication caused in patients by healthcare professionals. Conversely, aging involves physical, psychological, social, and environmental changes. The continuous and simultaneous use of five or more medications by a single elderly patient (polypharmacy) constitutes a public health issue and should be consistently studied in this population. Objectives: To correlate polypharmacy with iatrogenic in the elderly in Brazil and characterize it as a public health issue, assessing its impact on quality of life, analyzing its recurrence and predisposing risk factors, and discussing its main complications. Methodology: This study is a literature review conducted through a bibliographic survey on PubMed, VHL (Virtual Health Library), SciELO (Scientific Electronic Library Online), and Lilacs (Latin American and Caribbean Health Sciences Literature) platforms. Publications were selected in Portuguese, English, or Spanish, between 2019 and 2023, using the descriptors "Aged," "iatrogenic disease," "Anti-inflammatory Agents," and "public health," combined through the Boolean operator “AND.” Results: Polypharmacy has become increasingly common and is associated with various health issues, including falls, cognitive impairments, depression, malnutrition, resistant infections, mobility loss, auditory and visual difficulties, dizziness, and even premature death. Conclusion: It can be concluded that iatrogenic caused by polypharmacy is preventable, and rational drug use should be promoted. Furthermore, the biological vulnerability of the elderly must be studied and disseminated to mitigate these risks.